The Effect Of Home Country Economic Push Factors On Intention To Migrate: The Mediating Role Of Psychological Distress Among Professionals: A Conceptual Framework - Sabti, Yousif Mousa; Ramalu, Subramaniam Sri (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
Purpose: The purpose of the study is to examine the influence of home country economics push factors on the intention to migrate among professionals, the mediating effect of psychological distress. Methodology: This paper explores the effect of home country economics push factors on intention to migrate through previous literature. Results: This study considers appropriate propositions to enhance the professional‘s intention to migrate. The study develops related propositions, the home country economics push factors enhance the intention of migration. Implications: Understanding professional’s intentions to migrate are crucial for the hospital management for the real motives behind professional’s intentions to migrate, which will suggest them to make appropriate decisions. The suggestion eventually used for developing a conceptual framework for future empirical research.